Health Equity Rounds: An Interdisciplinary Case Conference to Address Implicit Bias and Structural Racism for Faculty and Trainees - Joanna Perdomo; Destiny Tolliver; Heather Hsu; Yuan He; Katherine A. Nash; Stephanie Donatelli; Camila Mateo; Cynthia Akagbosu; Faraz Alizadeh; Alexandra Power-Hays; Tyler Rainer; Daniel J. Zheng; et al. (Association of American Medical Colleges, 2019)
Introduction The medical community recognizes the importance of confronting structural racism and implicit bias to address health inequities. Several curricula aimed at teaching trainees about these issues are described in the literature. However, few curricula exist that engage faculty members as learners rather than teachers of these topics or target interdisciplinary audiences. Methods We developed a longitudinal case conference curriculum called Health Equity Rounds (HER) to discuss and address the impact of structural racism and implicit bias on patient care. The curriculum engaged participants across training levels and disciplines on these topics utilizing case-based discussion, evidence-based exercises, and two relevant conceptual frameworks. It was delivered quarterly as part of a departmental case conference series. We evaluated HER's feasibility and acceptability by tracking conference attendance and administering postconference surveys. We analyzed quantitative survey data using descriptive statistics and qualitatively reviewed free-text comments. Results We delivered seven 1-hour HER conferences at our institution from June 2016 to June 2018. A mean of 66 participants attended each HER. Most survey respondents (88% or more) indicated that HER promoted personal reflection on implicit bias, and 75% or more indicated that HER would impact their clinical practice. Discussion HER provided a unique forum for practitioners across training levels to address structural racism and implicit bias. Our aim in dissemination is to provide meaningful tools for others to adapt at their own institutions, recognizing that HER should serve as a component of larger, multifaceted efforts to decrease structural racism and implicit bias in health care.